Urinary Retention Due to Hematocolpos - Silva, Íris Santos (2021)
Hematocolpos is an obstruction of the menstrual flow due to an anomaly of the genital tract, with imperforate hymen being the most common one. It is an uncommon condition, with a prevalence of 1:1000 – 1:16 000. It is usually an asymptomatic condition until the onset of menarche, when there is accumulation of blood in the vagina (hematocolpos) or in the uterus (hematometra). A rare symptom of hematocolpos could be urinary retention. Our case report is about a 12-year-old girl, with no menarche and Tanner stage M4/P5, who was admitted to our emergency department with abdominal pain and urinary retention. A brief review of this rare condition is presented, in order to remind clinicians about its existence, so that it can be diagnosed and treated as quickly as possible.